Developing and Sustaining an Effective and Resilient Oncology Careforce: Opportunities for Action. (5th April 2020) - Takvorian, Samuel U; Balogh, Erin; Nass, Sharyl; Valentin, Virginia L; Hoffman-Hogg, Lori; Oyer, Randall A; Carlson, Robert W; Meropol, Neal J; Sheldon, Lisa Kennedy; Shulman, Lawrence N
Abstract: Advances in cancer care have led to improved survival, which, coupled with demographic trends, have contributed to rapid growth in the number of patients needing cancer care services. However, with increasing caseload, care complexity, and administrative burden, the current workforce is ill equipped to meet these burgeoning new demands. These trends have contributed to clinician burnout, compounding a widening workforce shortage. Moreover, family caregivers, who have unique knowledge of patient preferences, symptoms, and goals of care, are infrequently appreciated and supported as integral members of the oncology "careforce." A crisis is looming, which will hinder access to timely, high-quality cancer care if left unchecked. Stemming from the proceedings of a 2019 workshop convened by the National Cancer Policy Forum of the National Academies of Sciences, Engineering, and Medicine, this commentary characterizes the factors contributing to an increasingly strained oncology careforce and presents multilevel strategies to improve its efficiency, effectiveness, and resilience. Together, these will enable today's oncology careforce to provide high-quality care to more patients while improving the patient, caregiver, and clinician experience.